Konsep Life Skills dalam Pembelajaran Bahasa Arab di Madrasah - Muhammad Mas'ud (IAIN Salatiga, 2017)
This research uses qualitative descriptive approaching method and use study case research type. The data obtained from primary and secondary data sources, which data collection techniques are observation, interview, and documentation. The results of the research stated that in the life skill education design in the Arabic Language Learning at MI NU Tamrinut Thullab Undaan Kudus are: The aspects of life skills that will be developed are integrated and will be a part of the basic competencies that must be pursued accomplished with the achievement skills derived from the substance of the subject matter of Arabic Language Learning which is outlined into Prota, Promes, SK and KD Mapping, Syllabus, and RPP form. Implementation of life skill education in Arabic Language Learning at MI NU Tamrinut Thullab Undaan Kudus; according to the physiological and psychological level of students at the MI, it is emphasized on efforts to develop generic skills such as personal skills and social skills. While the supporting factors in the Life Skill Education implementation in Arabic Language Learning at MI NU Tamrinut Thullab Undaan Lor Undaan Kudus are: (1) Madrasah Religious Program; (2) Self Development Program in Madrasah; (3) Madrasah Cultural Development Program; (4) Most students have been studied at Diniyyah / TPQ. Whereas, the obstacles factors in the life skills education implementation in Arabic Language Learning at MI NU Tamrinut Thullab Undaan Lor Undaan Kudus are: (1) The lack of funds and facilities; (2) Educators are less motivated to be creative and innovative for using and developing learning strategies.